Bridal Palace/ Mohd Amiey Zulaieka Mohd Taip… [et.al.] - Mohd Taip, Mohd. Amiey Zulaieka; Wahap, Mohamad Zulfadhli; Uzir@ Nik Kamaruddin, Nik Zirhazaima; Salleh, Shahardin; Ismail, Shahniza; Syed Yusuf, Syarifah Khairunnisa Firdausyiah (2009)
Administration can be considered as one of the essential department in order to have an efficient and complete method of management. In any organization or business, administration played an important role to set up the business. A good management must ensure that all the partners or workers are able to work and cooperate with each other. The effectiveness of the management are the important aspect that we need to be taken care of and we are also trying our best in preparing this business proposal and hope to fulfil our mission and vision.